2009
DOI: 10.1007/s10979-008-9166-4
|View full text |Cite
|
Sign up to set email alerts
|

Police lie detection accuracy: The effect of lie scenario.

Abstract: Although most people are not better than chance in detecting deception, some groups of police professionals have demonstrated significant lie detection accuracy. One reason for this difference may be that the types of lies police are asked to judge in scientific experiments often do not represent the types of lies they see in their profession. Across 23 studies, involving 31 different police groups in eight countries, police officers tested with lie detection scenarios using high stakes lies (i.e., the lie was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 50 publications
1
84
0
1
Order By: Relevance
“…Many aspects of microexpressions need to be elucidated in the future including the lower limit, individual differences in expression and recognition of microexpressions (Bond and DePaulo, 2008;O′Sullivan et al, 2009;Wang and Fu, 2009;Warren et al, 2009), effective methods of training and the retention of training effects (Hurley, 2010;Matsumoto and Hwang, 2011), and automatic brief facial expression analysis systems (Polikovsky et al, 2010;Wu et al, 2010). As for individual differences, in groups closely related to deception detection, such as crime interrogators, national security personnel, visa interviewers, sales personnel, negotiators, and mental health professionals, the expression and recognition of microexpressions might not be the same as for other people.…”
Section: Discussionmentioning
confidence: 99%
“…Many aspects of microexpressions need to be elucidated in the future including the lower limit, individual differences in expression and recognition of microexpressions (Bond and DePaulo, 2008;O′Sullivan et al, 2009;Wang and Fu, 2009;Warren et al, 2009), effective methods of training and the retention of training effects (Hurley, 2010;Matsumoto and Hwang, 2011), and automatic brief facial expression analysis systems (Polikovsky et al, 2010;Wu et al, 2010). As for individual differences, in groups closely related to deception detection, such as crime interrogators, national security personnel, visa interviewers, sales personnel, negotiators, and mental health professionals, the expression and recognition of microexpressions might not be the same as for other people.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the results might have been different if the receivers were professional interviewers or investigators who were trained to detect lies and had experience with lie detection. Although some previous literature has reported that law-enforcement and non-law-enforcement individuals showed similar levels of deception accuracy [4], others have reported that trained detectives were more accurate in detecting deceit [14], particularly when they are asked to judge high stakes lies [17]. To verify training or experience effects on what we reported in our study, testing skilled vs. nonskilled receivers may contribute to a better understanding of our findings.…”
Section: Discussionmentioning
confidence: 49%
“…This prediction is based on research which indicates that behavioural differences between truth-tellers and liars may increase when there is motivation to provide an accurate or convincing account, such as receipt of positive (monetary) or negative incentives (avoidance of incidents with campus security; e.g., Bradley, 1988;Colwell, Hiscock-Anisman, Memon, Taylor, & Prewett, 2007), or when the stakes of providing an account are high (e.g., O'Sullivan, Frank, Hurley, & Tiwana, 2009;Vrij & Mann, 2001). …”
Section: Hypotheses: Experiments Resultsmentioning
confidence: 99%